Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Warung Subak Denpasar - Sugiarta, I Putu; Widagda, IG.N Jaya Agung (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
The business of food service in Denpasar has very rapid growth, from small-scale to large scale. The influence of service quality on consumer satisfaction in the Warung Subak is the purpose of this study. Total sample of 85 respondents. Multiple linear regression is used to analyze the data. The results showed direct evidence, reliability, responsiveness, assurance and empathy are jointly significant effect on consumer satisfaction at Warung Subak, Denpasar. Direct evidence, reliability, responsiveness, assurance and empathy partially significant effect on consumer satisfaction at Warung Subak. Empathy is the dominant independent variables that influence consumer satisfaction at Warung Subak, Denpasar. Management in order to improve service, hospitality, keep the faith and create a good corporate image to the consumer. Keywords: direct evidence, reliability, responsiveness, assurance, empathy, satisfaction, consumer